KEPERCAYAAN MEREK DAN BRAND AFFECT SEBAGAI ANTESEDEN DARI LOYALITAS MEREK - Rahayu, Sri; Harsono, Mugi (Media Ekonomi, 2018)
The purpose of this paper is to explain the important role of brand and brand loyalty in marketing activities. This paper also explains the antecedents of brand loyalty. The role of a brand does not only actas a name, but also increasing the company's competitive advantage. The benefits of a brand for consumers are, among many others, for emotional, self and social expression, attitudes, values and culture benefits. In the mean time, the role of brand loyalty in marketing is to contribute to the survival of the company, to increase new customer opportunities as well as to reduce marketing costs. To improve a brand loyalty, a companyshould increase its brand trust in advance as it plays an important role in improving brand loyalty. A cpmpany brand trust has two dimensions of intention and reliability. Brand affect, on the other hand, is an important for improving a brand loyalty. Therefore,a company’sbrand trust and brand affect should be improved for the brand loyalty to improve as well. Key words : Brand trust, Brand Affect, Brand Loyalty